ZOE: Fast cardinality estimation for large-scale RFID systems - Zheng, Yuanqing. (2013)
Estimating the RFID cardinality with accuracy guarantee is an important task in large-scale RFID systems. This paper proposes a fast RFID cardinality estimation scheme. The proposed Zero-One Estimator (ZOE) protocol rapidly converges to optimal parameter settings and achieves high estimation efficiency. ZOE significantly improves the cardinality estimation efficiency, achieving 3x performance gain compared with existing protocols. Meanwhile, ZOE guarantees arbitrary accuracy requirement without imposing computation and memory overhead at RFID tags. Due to the simplicity and robustness, the ZOE protocol provides reliable cardinality estimation even over noisy channel. We implement a prototype system using the USRP software defined radio and Intel WISP RFID tags. We also evaluate the performance of ZOE with extensive simulations. The evaluation of ZOE shows encouraging results in terms of estimation accuracy, time efficiency, as well as robustness.